An Explanation of Port Activity on the South Shore of the Lower St.Lawrence Rive - Slack, B. (Cahiers de géographie du Québec, 1973)
The study examines the factors that affect variations in port size in the region below Québec City on the south shore of the St. Lawrence River. The investigation draws upon the results of earlier studies and measures the relationships between six factors and port size. Multiple regression analysis produces a model that accounts for over 90 per cent of size variation in the port System.